2015
DOI: 10.1007/s10854-015-3618-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel sol–gel method for synthesis of PbTiO3 and its light harvesting applications

Abstract: A novel two-step sol-gel method was used in order to synthesize PbTiO 3 nanoparticles with aid of Pb(CH 3 COO) 2 Á2H 2 O, and Ti(OC 4 H 9 ) 4 (TNBT) as the starting reagents in the presence of ethanol as the solvent. To the best of authors knowledge, it is first time that benzene-1,3,5-tricarboxylic acid [C 6 H 3 (COOH) 3 ] (trimesic acid) use as a chelate agent in produce lead titanate nanoparticles. Besides, to examine the effect of some reaction parameters such as surfactants, reaction temperature, and mola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 33 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…Figure a (the untreated sample) contains three wide absorption bands at around 847.58, 1628.59 and 3445.16 cm −1 , while with the calcinated sample (Fiure 3b) these bands were weakened, indicating the evaporation of adsorbed water . The calcinated sample further contains band corresponding to the scheleete type structure between 950 and 460 cm −1 (950.0, 862.1, 738.2, 694.6, 481.1, 458.8, 417.2) …”
Section: Resultsmentioning
confidence: 99%
“…Figure a (the untreated sample) contains three wide absorption bands at around 847.58, 1628.59 and 3445.16 cm −1 , while with the calcinated sample (Fiure 3b) these bands were weakened, indicating the evaporation of adsorbed water . The calcinated sample further contains band corresponding to the scheleete type structure between 950 and 460 cm −1 (950.0, 862.1, 738.2, 694.6, 481.1, 458.8, 417.2) …”
Section: Resultsmentioning
confidence: 99%
“…150 In another study, Nasab et al have also used trisemic acid as a chelating agent in the sol−gel synthesis of PbTiO 3 . 151 Doggali and co-workers have synthesized A-site K + , Ce 4+ , and Ba 2+ substituted PrMnO 3 by using the sol−gel technique and found that the surface area of thus obtained perovskites was entirely dependent on the nature of the substituting cation. 152…”
Section: Strategies Employed In the Synthesis Of Perovskite Oxide Bas...mentioning
confidence: 99%
“…The PEC cell was a two electrode system, TiO 2 is a working electrode with active surface area of 1 cm 2 , Graphite as a counter electrode and 0.1 M NaOH was used as an electrolyte illuminated by 5 mW/cm 2 intensity UV source [29].…”
Section: Solar Cell Fabricationmentioning
confidence: 99%